EVOLUTION OF THE HUMUS CLAYEY MATERIAL OF THE CHERNOZEM HORIZON DURING LAND RECLAMATION OF SOLONETZES BY GROUNDING - N. Chizhikova; N. Khitrov; Yu. Cheverdin (Бюллетень Почвенного института им. В.В. Докучаева)
Under the influence of the saline process (sodium exchange rate of 5-15% and specific electrical conductivity of the extract from the water-saturated paste ECse < 2 dSm/m) the well aggregated black earth material used for soil reclamation by means of hydromorphous black earth salt complexes starts to turn into a peptized state and is evolutionarily transformed into a texture-differentiated profile of saline soil. Part of the previously aggregated silt passes to the water-performed state and begins to move down the profile from 0-4 cm layer. Water-performed sludge consists of highly ordered complex mixed mica-smektite formations with a high content of smectite packets, hydro-mica, kaolinite, chlorite, as well as highly dispersed quartz. A distinctive feature of the soil surface horizons of the solonetz complex is the increased content of highly dispersed quartz of micron dimension. The composition of mineral components in the aggregated muds remains the same, but the share of hydro-mica increases, and mixed-layer mica-smektites have a more perfect structure due to less disordered structure in crystallites. The share of finely dispersed quartz in the aggregated silt fraction is less than that of water-peptized silt, and is more similar to that of loess-like loess-like loam, which is a soil-forming rock.